An 18‐year climatology of hailstorm trends and related drivers across southeast Queensland, Australia. (January 2017) - Soderholm, J. S.; McGowan, H.; Richter, H.; Walsh, K.; Weckwerth, T. M.; Coleman, M.
Abstract : The southeast Queensland (SEQ) region of Australia is recognised for frequent thunderstorms documented through numerous studies including high‐impact severe thunderstorm cases which have caused insured losses exceeding 1 billion AUD. Despite a modest body of scientific literature, basic questions regarding the role of climate, synoptic and local‐scale (<10 km) processes affecting the variability of thunderstorms still remain. In an effort to advance these questions as part of the Coastal Convective Interactions Experiment (CCIE), this study integrates multiple datasets across an 18‐year period (July 1997–June 2015) to provide a mesoscale climatological analysis of the SEQ hailstorms and associated environmental conditions. On a multi‐year time‐scale, the relationship between the El Niño Southern Oscillation and hailstorm frequency is consistent with previous studies. On synoptic scales, a southeasterly change situation coupled with a sea breeze was found to provide the most favourable environment for hailstorms, particularly for southwest SEQ. On the local scale, hail development within convective cells was found to be most frequent within the inland limb of the maritime air mass on sea‐breeze days. This observation suggests the sea‐breeze air masses may become favourable for convection after sufficient modification during inland propagation.